ART GALLERY DI KABUPATEN KUBU RAYA - Prantano, Muhammad Adam Brilliant; Affrilyno, Affrilyno; Purnomo, Yudi (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2025)
The people of Kubu Raya Regency are already familiar with art. The Kubu Raya Regency Government often organizes art activities such as holding art competitions held by the government for the people of Kubu Raya Regency who have enthusiasm for art. However, this is still not in line with the facilities available to artists or art activists in terms of developing potential and providing a forum for artists. Therefore, the development of existing potential needs to be done by inserting it in the tourism sector, namely the development of Art Gallery built in Kubu Raya Regency. The design of the existing Art Gallery is a form of response to the development of potential as well as problem solving in Kubu Raya Regency by emphasizing case studies of similar objects with the aim of enriching design ideas in design and some existing standards so that the design of this Art Gallery is in accordance with applicable regulations. The result of this design is an Art Gallery area that can accommodate the focus of community art activities, and design buildings that are in accordance with the context of needs, artistic values, and space requirements. The design of the Art Gallery building also considers aspects of the location that are adjusted to the Kubu Raya Regency RTRW as the location of the tourist development of Kubu Raya Regency so that it is still in line with the development plan of the Kubu Raya Regency area.